2020
DOI: 10.1093/neuros/nyaa313
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Anatomic Segment Involvement on Stereotactic Radiosurgery for Facial Nerve Schwannomas: An International Multicenter Cohort Study

Abstract: BACKGROUND Facial nerve schwannomas are rare, challenging tumors to manage due to their nerve of origin. Functional outcomes after stereotactic radiosurgery (SRS) are incompletely defined. OBJECTIVE To analyze the effect of facial nerve segment involvement on functional outcome for these tumors. METHODS Patients who underwent single-session SRS for facial ner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…Studies have suggested that with a treatment goal of preventing the tumor growth while preserving function of facial nerve in FNS, surgery poses a higher risk of facial palsy compared to SRS for facial nerve function [14]. Further, multi-institutional studies have demonstrated that SRS can result in durable tumor control 87.2-92% and facial nerve functional preservation of approximately 90-94% [15][16][17]. No study to date has assessed the relationship of hfSRS to radiological and functional outcome in FNS.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have suggested that with a treatment goal of preventing the tumor growth while preserving function of facial nerve in FNS, surgery poses a higher risk of facial palsy compared to SRS for facial nerve function [14]. Further, multi-institutional studies have demonstrated that SRS can result in durable tumor control 87.2-92% and facial nerve functional preservation of approximately 90-94% [15][16][17]. No study to date has assessed the relationship of hfSRS to radiological and functional outcome in FNS.…”
Section: Discussionmentioning
confidence: 99%
“…Facial nerve schwannomas were differentiated from vestibular nerve schwannomas by intraoperative findings or by neurological features and radiologic characteristics. 1,3 Facial nerve schwannoma patients had more facial nerve function deficits along with tumor involvement of the temporal bone or extra temporal segments. 3 All imaging was reviewed by experienced neuroradiologists, as well as radiosurgical teams practicing at tertiary or quaternary referral centers.…”
Section: Patient Populationmentioning
confidence: 97%
“…A different cohort with a distinctly different analytic approach was presented in a prior study. 1 Of the 63 patients included in that study, eight patients managed with decompressive (8/55, 14.5%) surgery and/or multi-session radiosurgery were excluded. In the current study, a retrospective analysis was performed on 55 patients, treated with SRS alone (43 patients) or resection followed by SRS (12 patients), either because of tumor progression or as an adjuvant.…”
Section: Patient Populationmentioning
confidence: 99%
“…Stereotactic radiosurgery has shown very good control rates (90-100%) for facial nerve schwannoma [27,37,44,54,73]. A recent multicentre retrospective study by Mehta et al [51] studied 63 patients who had SRS for facial nerve schwannomas. At last follow-up, 48% of tumours were stable, 46% had regressed, and 6% had progressed.…”
Section: Stereotactic Radiosurgerymentioning
confidence: 99%